2005
DOI: 10.1007/s11104-004-1307-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various salt-alkaline mixed stresses on Aneurolepidium chinense (Trin.) Kitag.

Abstract: The stress conditions of salt-alkalinized soil were simulated to investigate the features and acting factors of saltalkaline mixed stress, using a natural salt-alkaline tolerant grass Aneurolepidium chinense (Trin.) Kitag. According to the features of salt-alkalinized soil in the northeast of China, various salt-alkali conditions with different salinities and pHs were established by mixing NaCl, NaHCO 3 , Na 2 SO 4 , and Na 2 CO 3 , in various proportions. The treatments included a salt concentration range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
176
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(193 citation statements)
references
References 19 publications
16
176
1
Order By: Relevance
“…Liu et al [25] carried out a field experiment to determine the effect of dry saving on rice yield on a salt-affected soil in a yellow river irrigation area of Ningxia and their results showed that dry saving led to a rise in rice production. However, saline-sodic soil dominated by carbonate and bicarbonate salts in Songnen plain becomes alkaline and the combination of salinity and alkalinity may be more harmful than either alone [37]. Thus, dry saving may not be suitable for this soil as it would cause high salt concentration in root zone and then constrain crop growth and bring about yield loss.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [25] carried out a field experiment to determine the effect of dry saving on rice yield on a salt-affected soil in a yellow river irrigation area of Ningxia and their results showed that dry saving led to a rise in rice production. However, saline-sodic soil dominated by carbonate and bicarbonate salts in Songnen plain becomes alkaline and the combination of salinity and alkalinity may be more harmful than either alone [37]. Thus, dry saving may not be suitable for this soil as it would cause high salt concentration in root zone and then constrain crop growth and bring about yield loss.…”
Section: Introductionmentioning
confidence: 99%
“…Plants accumulate cations, such as Na + and K + , and simultaneously accumulate inorganic anions, such as Cl - (Ghoulam et al 2002, Melgar et al 2008, or synthesize organic anions (Sagi et al 1997) to keep ion balance. Previous studies have shown that to maintain pH stability, organic acid accumulation may be an important means for some plants, such as Aneurolepidium chinense (Shi and Wang 2005). Osmotic stress leads to the formation of ROS.…”
mentioning
confidence: 99%
“…The 100 cuttings of each population were divided into five groups, and each group (four replications of five cuttings per replication for each population) was exposed to one of the five treatments. Two neutral salts (NaCl and Na 2 SO 4 ) and two alkaline salts (NaHCO 3 and Na 2 CO 3 ) were selected and mixed in various proportions according to Shi and Wang (2005). Plants in one treatment group were watered with Hoagland nutrient solution as control, while plants in the other four groups were watered with nutrient solution containing different salt mixtures which represent the pH 7.9, 8.8, 9.8 and 10.4 treatments.…”
mentioning
confidence: 99%
“…Alkali stress is the stress of alkaline salts (NaHCO 3 and Na 2 CO 3 ) and salt stress can be defined as the stress of neutral salts (NaCl and Na 2 SO 4 ) (Yang et al, 2007). When saline soil contains CO 3 2-and/or HCO 3 -, it causes injury to plants not only through salt stress, but also through alkali stress (Li et al, 2010a and b;Shi and Wang, 2005). The existence of alkali stress has been demonstrated clearly by a number of studies, which have shown it to be more severe than salt stress (Campbell and Nishio, 2000;Brand et al, 2002).…”
Section: Introductionmentioning
confidence: 99%